The value of synovial fluid analysis in the assessment of knee joint destruction in arthritis in a three year follow up study - Aman, S (1999)
OBJECTIVES—To assess the predictive significance of synovial fluid (SF) analysis for progressive radiological knee joint destruction in arthritis. METHODS—Altogether 55 patients with arthritis and knee joint effusion were included in the study. The diagnosis was rheumatoid arthritis (RA) for 44 of them, chronic seronegative spondylarthropathy for seven and juvenile rheumatoid arthritis for four. The mean age of the patients was 51.8 (SD 14.9, range 19-82) years, and the mean duration of disease 10.9 (SD 9.2, range 0.5-37) years. In addition to the routine laboratory tests, different markers of collagen synthesis and breakdown in serum and SF were assessed. The radiological grade of the knee joint was assessed by Larsen's method at the baseline and after a three year follow up. RESULTS—During the follow up, Larsen's grade deteriorated in 22 (40%) patients. These patients had a significantly higher median level of cross linked carboxyterminal telopeptide of type I collagen (ICTP) in SF at entry than those who had a stable index (p = 0.035). Serum ICTP did not have any predictive value for a specific joint. The median levels of total SF leucocytes (p = 0.012) and the subgroup of polymorphonuclear leucocytes (p = 0.018) were higher in the patients with a stable Larsen's index. However, the relation of SF leucocyte level to radiological progression could not be confirmed in the RA group. CONCLUSION—It is concluded that SF analysis may help in the identification of patients with inflammatory arthritis who are at risk for progressive destruction in a particular joint. A high total SF leucocyte level is not necessarily associated with a poor prognosis. Instead, a high SF ICTP level seems to reflect accelerated bone degradation.